PENERAPAN SISTEM MOVING CLASS PADA PROSES PEMBELAJARAN MATA PELAJARAN EKONOMI - Reisza Kinantaka, (Pendidikan Ekonomi, 2013)
Nation of KBK and KTSP as the new curriculum leads the students to be more active, thus the one way learning process is not be used anymore. Moving class is the learning system in which the students themselves come to a certain teachers class. The method used in this research is descriptive by describing the implementation of moving class in SMA Muhammadiyah 2 Surabaya and so does the students response on it. The observation sheet for students activity, teacher activity, and students questionnaire is used for gathering the data. The result of this research shows that the moving class implementation had run well. The media used and other facilities made students felt comfort during the class. While running the moving class, teacher no needed to be in class during the substitution. Moreover, students showed their enthusiasm on Moving class system.